2022
DOI: 10.1007/s12032-022-01875-w
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic nuclear divisions 1 promotes proliferation and metastasis in hepatocellular carcinoma and is a potential diagnostic and therapeutic target gene

Abstract: Hepatocellular carcinoma is the cancer with the highest incidence among liver cancers and how to treat this cancer effectively is still a difficult problem we must face. We selected meiotic nuclear divisions 1 (MND1) as the study object by combining data from The Cancer Genome Atlas (TCGA) database with prognostic survival analysis. We validated the value of MND1 in evaluating the prognosis of hepatocellular carcinoma through a diagnostic and prognostic model. At the same time, cellular experiments were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
(40 reference statements)
0
0
0
Order By: Relevance
“…Fang et al, 11 Bao et al 13 and Tan et al 39 found that the MND1 mRNA expression level was significantly elevated in a variety of tumors through the TIMER database, including bladder urothelial carcinomas (BLCA), breast invasive carcinomas (BRCA), cervical squamous cell carcinomas and endocervical adenocarcinomas (CESC), cholangiocarcinoma (CHOL), colon adenocarcinomas (COAD), esophageal carcinomas (ESCA), glioblastoma multiforme (GBM), head and neck squamous cell carcinoma (HNSC), kidney chromophobe (KICH), kidney renal clear cell carcinoma (KIRC), kidney renal papillary cell carcinoma (KIRP), liver hepatocellular carcinoma (LIHC), lung adenocarcinoma (LUAD), lung squamous cell carcinoma (LUSC), pheochromocytoma and paraganglioma (PCPG), prostate adenocarcinoma (PRAD), rectum adenocarcinoma (READ), stomach adenocarcinoma (STAD), thyroid carcinoma (THCA) and uterine corpus endometrial carcinoma (UCEC) ( Figure 1A ). Since some tumors lack normal tissue data in the TIMER database, we further assessed the differences in MND1 expression between tumors and normal tissues using the GTEx dataset in the GEPIA database.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fang et al, 11 Bao et al 13 and Tan et al 39 found that the MND1 mRNA expression level was significantly elevated in a variety of tumors through the TIMER database, including bladder urothelial carcinomas (BLCA), breast invasive carcinomas (BRCA), cervical squamous cell carcinomas and endocervical adenocarcinomas (CESC), cholangiocarcinoma (CHOL), colon adenocarcinomas (COAD), esophageal carcinomas (ESCA), glioblastoma multiforme (GBM), head and neck squamous cell carcinoma (HNSC), kidney chromophobe (KICH), kidney renal clear cell carcinoma (KIRC), kidney renal papillary cell carcinoma (KIRP), liver hepatocellular carcinoma (LIHC), lung adenocarcinoma (LUAD), lung squamous cell carcinoma (LUSC), pheochromocytoma and paraganglioma (PCPG), prostate adenocarcinoma (PRAD), rectum adenocarcinoma (READ), stomach adenocarcinoma (STAD), thyroid carcinoma (THCA) and uterine corpus endometrial carcinoma (UCEC) ( Figure 1A ). Since some tumors lack normal tissue data in the TIMER database, we further assessed the differences in MND1 expression between tumors and normal tissues using the GTEx dataset in the GEPIA database.…”
Section: Resultsmentioning
confidence: 99%
“…Abnormally high expression of MND1 correlated with poor OS, DSS, and PFI in multiple cancers. According to the available studies, MND1 is highly expressed in STAD, 47 BRCA, 13 LUAD, 2 KIRC, 11 LIHC 39 and other tumors and is associated with patient prognosis, while our pan-cancer study found that, in addition to the reported tumors, MND1 is also highly expressed in ACC, HNSC, LGG and other tumors, which is related to the poor prognosis of the patients, suggesting that MND1 may play an important role in a wide range of tumors. This indicates that MND1 may play an important role in a variety of tumors, and further in-depth studies are needed to explore the role of MND1 in these tumors.…”
Section: Discussionmentioning
confidence: 99%